Implementation of Story Telling Method to Improve Student Learning Outcomes on Tolerance Material in Islamic Religious Education Lessons at SMP Negeri 2 Hutaraja Tinggi - Nengsih, Wahyu; Wulandari, Nanda Ugig; Mustofa, Asyik; Priyatni, Ida; Azizah, Zuhrotul (MANDAILING GLOBAL EDUKASIA, 2024)
This study aims to improve student learning outcomes in tolerance material in Islamic Religious Education (PAI) subjects through the application of the storytelling method. This method is applied in class IX-1 of SMP Negeri 2 Hutaraja Tinggi, Padang Lawas Regency, with the hope of making learning more interesting and improving students' understanding of the concept of tolerance. The research approach used is Classroom Action Research (CAR) with the Kemmis and McTaggart model, which consists of two cycles. Each cycle includes the planning, implementation, observation, and reflection stages. The results of the study showed that the application of the storytelling method was able to significantly improve student learning outcomes. In the first cycle, the percentage of student learning completion was still relatively low, but after improvements in the second cycle, there was a significant increase in terms of both conceptual understanding and student participation in learning. In addition, this method also creates a more enjoyable, interactive learning atmosphere, and motivates students to be more active in discussing and expressing opinions. Based on the findings of this study, it can be concluded that the storytelling method is effective in improving student learning outcomes in tolerance material in PAI subjects. Teachers are expected to be able to apply this method as an alternative in learning to create a more communicative and meaningful atmosphere for students